Implications of primary science curriculum development in teachers' college programmes - Walker, E. E. (Caribbean Regional Science Project, 1978)
This paper discusses the implications of primary science curriculum development for training college programmes in science. Problems encountered at the training college are listed. The new role of the teacher, guidelines, and standards for the training programme, and areas for investigation are highlighted
Keywords: Teachers colleges